EVALUASITERHADAPPERANCANGAN SISTEM INFORMASI CRM UNTUK IKM Studi Kasus di IKM Tas Yanri Bogor - Andriariza, Yan (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
CRM is a business process that gave priority to relations with customers. The presence of CRM-based information systems in /KM to help /KM to get closer to its customers. Through this research will be evaluated the importance of CRM. With the CRM-based Information System will provide marry benefits, among others, is an automated process, marketing the more spacious, and customers can more easily communicate with the /KM in these.